Navigating recovery while postpartum: examining the relationship between maternal functioning and substance use disorders - Leah A. Holcomb; Rachel Mayo; Bonnie Treado; Jennifer Barkin; Kathleen Cartmell; Lori Dickes; Lior Rennert (Journal of Psychosomatic Obstetrics and Gynecology)
Our current understanding of postpartum people’s functioning while managing substance use disorder (SUD) recovery is limited. This study explored whether having a SUD impacts maternal functioning and examined the reliability of the Barkin Index of Maternal Functioning (BIMF) in postpartum people with SUDs. We conducted a prospective, cross-sectional survey (n = 141) by administering the BIMF and a demographic questionnaire with a sample of postpartum people with SUD (n = 48) and a comparative sample of postpartum people without SUD (n = 93). The internal reliability (Cronbach’s alpha = .86) was consistent with previous studies. SUD diagnosis was significantly associated with lower functioning, with individuals in the SUD group having an 8-point lower BIMF score compared to persons without SUDs, although both groups reported moderately high BIMF scores (>80). While not statistically significant, participants with SUDs had reduced functioning scores over time. Considering the increasing rate of overdose deaths in postpartum persons, further examination of functioning in postpartum persons with SUDs is warranted. Integration of the BIMF into SUD screening and treatment can provide a holistic view of postpartum experiences in this high-risk population and serve as a unique tool to understand the needs of new mothers navigating SUD recovery.